PENYELESAIAN KLAIM DAN SUBROGASI OLEH SURETY COMPANY TERHADAP PRINCIPAL WANPRESTASI DALAM PERJANJIAN SURETY BOND - Abdul Rahman (HUKUM PEMBANGUNAN EKONOMI, 2021)
This research aims to examine the problems in the disbursement of Surety Bond claims by oblige against PT Askrindo Persero against the principal who wanprestasi in the implementation of the funneling work. As for this research, using empirical methods and descriptive analytical that provide an overview of certain symptoms in order to get the data as accurate as possible. Data collection techniques are carried out by Literature material Studies and Interviews to Underwriting Staff. The results of the study, against the settlement of Conditional Claims are not in line with Presidential Regulation No. 12 of 2021 which requires one of them is easy to disburse. The problem of recovery implementation experienced by Surety Company in surety bond guarantee is the absence of special arrangements regarding subrogation rights owned by Surety Company as a guarantor.